Contiguità territoriale e shock sul consumo nelle regioni italiane - Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
– The hypothesis of complete consumption risk-sharing suggests that only uninsurable national and international disturbances should affect the growth of the regional consumption. Therefore, the correlation among regional consumption growth rates should be high.This work analyzes the issue of regional consumption risk-sharing in Italy over the period 1971-93. The empirical evidence is mixed: consumption correlations are high but other formal tests suggest the relevance of idiosincratic effects. In conclusion, the overall degree of consumption risksharing appears to be less than perfect.
Keywords: 330